The Effectiveness of Google Classroom On Writing Descriptive Text at Mts. Ma’arif Sidomukti Kebomas - Salamun, Salamun (JEET, Journal of English Education and Technology, 2023)
Writing skills have an important role as a communication system rather than as an object of study which has taken place in both second and foreign language settings. In this research, the focus is on students’ writing descriptive text to using Google Classroom on students’ writing descriptive text. The researcher conducted this research at Mts. Ma’arif Sidomukti Kebomas. The sample in this research was 34 students of 7.3 at Mts. Ma’arif Sidomukti. The researcher used the quantitative method by a pre-experimental design with given pre-test before treatment and post-test after treatment. Then data analysis using IBM SPSS v28.0 with the formula paired sample t-test. This showed that the average obtained by the post-test was higher than the pre-test. This indicated that the treatment was successful. It has paired T-test calculation researcher. T-test was calculated to determine the comparison of the two means between pre-test and post-test. From the table above, the value of Asymp. Sig. (2-tailed) is 0.001 at the critical value for the 5% level. This means that the significance value is less than 5% or (0.001<0.05). So, the null hypothesis can be rejected. It can be concluded that the study's google classroom media is effective.